Journal of Inflammation - Kirkham, Paul; Rossi, Adriano
Journal of Inflammation welcomes research submissions on all aspects of inflammation. The five classical symptoms of inflammation, namely redness (rubor), swelling (tumour), heat (calor), pain (dolor) and loss of function (functio laesa), are only part of the story. The term inflammation is taken to include the full range of underlying cellular and molecular mechanisms involved, not only in the production of the inflammatory responses but, more importantly in clinical terms, in the healing process as well. Thus the journal covers molecular, cellular, animal and clinical studies, and related aspects of pharmacology, such as anti-inflammatory drug development, trials and therapeutic developments. It also considers publication of negative findings. Journal of Inflammation aims to become the leading online journal on inflammation and, as online journals replace printed ones over the next decade, the main open access inflammation journal. Open access guarantees a larger audience, and thus impact, than any restricted access equivalent, and increasingly so, as the escalating costs of printed journals puts them outside University budgets. The unrestricted access to research findings in inflammation aids in promoting dynamic and productive dialogue between industrial and academic members of the inflammation research community, which plays such an important part in the development of future generations of anti-inflammatory therapies.